30. RESULTS OF SUPPLEMENTAL TREATMENT OF MFOLFOX 6 REGIMEN ON PATIENTS AFTER COLON CANCER SURGERY AT THE ONCOLOGY DEPARTMENT OF VIET DUC UNIVERSITY HOSPITAL, PERIOD 2015 TO 2022 (Vietnam Journal of Community Medicine, 2024)
Objective: Evaluate the results of adjuvant chemotherapy mFOLFOX6 regimen and monitor the survival time of colon cancer patients after surgery. Subject and method: Retrospective, descriptive study with 50 patients after colon cancer surgery using the mFOLFOX6 regimen. Results: The rate of tumor enlargement ≥ 5cm in the study group is over 50%, which means the larger the tumor, the higher the chance of recurrence, the worse the prognosis, affecting the patient’s survival time; 78% of patients after surgery have late-stage cancer (stages III and IV). 24% of patients have metastatic lymph nodes of 4 or more lymph nodes similar to stages III and IV. This proves that tumor size is also related to local recurrence rate and negatively affects survival of the patient if they do not receive adjuvant chemotherapy. Results after treatment immediately after 01 month of re-examination showed that 86% of patients did not relapse. This shows that the mFOLFOX6 post-operative adjuvant regimen has a high success rate. The survival time of patients after adjuvant treatment with mFOLFOX6 regimen was prolonged. Over 50% of patients in the study lived for 5 years or more and most of the patients are aged from 50 to 70 years old. Conclusion: Adjuvant chemotherapy mFOLFOX6 regimen in patients after colon cancer surgery is highly effective in treating 86% of patients living 3 years or more and 54% living more than 5 years.
Keywords: Adjuvant chemotherapy, colon cancer, the patient’s survival time.